A clinico-epidemiological study of HIV infected children in western Rajasthan - Mourya, Harish Kumar; Verma, Suresh Kumar; Mourya, Saroj; Nangal, Laxman (International Journal of Contemporary Pediatrics, 2017)
Background: Assessment of clinico demographic characteristics of HIV infected children in western Rajasthan. Methods:All the children who were attending Antiretroviral treatment (ART) center for one year period were enrolled for study as pre-ART and ART group. All the data pertaining to clinical and demographic characteristics were recorded. They were further classified into clinical staging as per WHO guideline and immunological staging based on CD4 count in accordance with CDC classification of immunodeficiency. Results: Perinatal transmission is the most common mode of acquiring HIV in Pediatric age, who most commonly presented with Fever and diarrhoea along with failure to thrive. Tuberculosis and oral candidiasis were the commonest opportunistic infections in this geographic area. Conclusions: A proper history, detailed clinical examination and high index of suspicion would therefore help in making early diagnosis to institute an appropriate management plan.